(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The formation of communication skills among students in the lessons of Russian as a foreign language is not possible without the study of phraseological units of Russian language - a nationally oriented unit of vocabulary. Based on the analysis of scientific and methodological literature, the author offers answers to topical questions related to the conditions for the selection of phraseological units, the time of their study in the structure of lessons and didactic methods of working with them.